"Haunted Still by Memories": John Eppel's Post-Settler Plant Poetic. Issue 4 (2nd October 2019) - Wylie, Dan
Summary: Bulawayo-based writer John Eppel is gaining increased prominence and acceptance as Zimbabwe's premier satirist, in both poetry and prose. Early critics, even fellow-poets, failed to read the coruscating and self-referential nature of that satire, and poems treating the natural world were too easily dismissed as Romantic "white" nostalgia. A closer reading reveals a subtler range of questions, exploring the relations between white or Rhodesian identity and nature (especially flowers), between satire and belonging, between seasonal ephemerality and political uncertainty, between literary allusion and sensual immediacy, poetic form and historical turbulence. Above all, many of Eppel's plant-focused poems treat the layered and conflicting demands of memory. This article explores these questions over thirty years of Eppel's production (from Spoils of War [1989] to Together [2011]) and through three interlocking phases or aspects: childhood, war and political transition, and post-Independence disillusionment.